Complementary Functions of Vanadium in Boosting Electrocatalytic Activity of CuCoNiFeMn High-Entropy Alloy for Water Splitting - Sivanantham, Arumugam; Lee, Hansung; Hwang, Sung Won; Lee, Han Uk; Cho, Sung Beom; Ahn, Byungmin; Cho, In Sun (Advanced Functional Materials, 2023)
High entropy alloys (HEAs) composed of multi-metal elements in a single crystal structure are attractive for electrocatalysis. However, identifying the complementary functions of each element in HEAs is a prerequisite. Thus, VxCuCoNiFeMn (x = 0, 0.5, and 1.0) HEAs are investigated to identify the active role of vanadium in improving the electrocatalytic activity for the hydrogen evolution reaction (HER). Structural studies show the successful incorporation of V in the HEA. V1.0CuCoNiFeMn (V1.0-HEA) shows an overpotential of 250 mV versus the reversible hydrogen electrode (at −50 mA cm−2, 1 m KOH), which is ≈170 mV lower than that of control-HEA (422 mV). Improves electrical conductivity and the electrochemical surface area of the V1.0-HEA accelerated HER activity. Furthermore, density functional theory calculations reveal reduced water dissociation and hydrogen adsorption energies of V1.0-HEA, resulting in the boosted HER kinetics. The effect of V incorporation on the barrier height and active sites at the surface of V1.0-HEA is schematically explained. This study can be facilitated for the development of highly active HEAs for large-scale electrochemical water splitting.
Keywords: Electrocatalytic activity; High entropy alloys; Hydrogen evolution reactions; Metal elements; Multi-metals; Overpotential; Single-crystal structure; Structural studies; Vanadium incorporation; Water splitting; CuCoNiFeMn; Gibbs free energy; high entropy alloys; hydrogen evolution reaction; vanadium incorporation